Identification and immunophenotype of abnormal cells present in focal cortical dysplasia type IIb - Gleice K. Sousa; Caroline S. Capitelli; Thaís C. D. Dombroski; César A. B. Zanella; Vera C. Terra; Tonicarlo R. Velasco; Hélio R. Machado; João A. Assirati; Carlos G. Carlotti; Vani M. Alves; Jaderson Costa DaCosta; André L. Palmini; et al. (BMC, 2018)
Abstract Background Focal cortical dysplasias (FCDs) are malformations of cortical development that present cortical dyslamination and abnormal cell morphology and are frequently associated with refractory epilepsy. FCD type IIb presents dysmorphic neurons (DNs) and balloon cells (BCs), which are the hallmarks of this dysplasia. Moreover, hypertrophic neurons (HyNs) may be present in FCD types I, II and III. The objective of this study was to perform a detailed morphology and immunophenotype study of BCs, DNs, and HyNs in a cohort of FCD IIb patients. Methods Cortices resected as a treatment for refractory epilepsy from 18 cases of FCD type IIb were analysed using Bielschowsky method and haematoxylin and eosin as routine stains. Immunophenotype was performed using specific antibodies to detect epitopes differentially expressed by abnormal cells. Results All cases showed cortical dyslamination, BCs, DNs, and HyNs. No cell layer or column could be identified, except for cortical layer I. Lesions predominated in the frontal cortex (11 cases). DNs were large neurons and presented a clumped and or displaced Nissl substance towards the cell membrane, and a cytoplasm accumulation of neurofilament that displaced the nucleus to the cell periphery, as shown by Bielschowsky staining and immunohistochemistry. HyNs were as large as DNs, but without alterations of Nissl substance or dense neurofilament accumulation, with a central nucleus. BCs were identified as large, oval-shaped and pale eosinophilic cells, which lacked the Nissl substance, and presented an eccentric nucleus. BCs and DNs expressed epitopes of both undifferentiated and mature cells, detected using antibodies against nestin, vimentin, class III β-tubulin, pan-neuronal filaments, neurofilament proteins, β-tubulin and NeuN. Only BCs expressed GFAP. Conclusion FCDs present with disorganization of the cerebral cortex architecture, abnormal cell morphology, are frequently associated with refractory epilepsy, and their post-surgical prognosis depends on the type of FCD. The diagnosis of focal cortical dysplasia in a surgical specimen relies on the identification of the abnormal cells present in a dysplastic cortex specimen. The current report contributes to the identification of balloon cells, dysmorphic and hypertrophic neurons in the context of focal cortical dysplasia type IIb.